2019
DOI: 10.1103/physrevb.99.014437
|View full text |Cite
|
Sign up to set email alerts
|

Engineering terahertz surface magnon-polaritons in hyperbolic antiferromagnets

Abstract: Magnetic crystals were recently studied as a route to hyperbolic dispersion and the effects associated with it. These studies, however, concentrated on bulk waves and frequencies where transmission is possible and where negative refraction occurs. Here, in contrast, we concentrate on geometries which sample regions of the dispersion relations where bulk propagation is not possible. This is done by controlling the orientation of the uniaxial anisotropy axis with respect to the surface of the crystal. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…[18,55] A related phenomenon that is often seen in magnetic insulators in this frequency range is the existence of surface waves. [56][57][58] Although this nonreciprocity on reflection is related to surface effects, we found that true surface waves only appear in this composite material if the conductivity was made smaller (σ < 10 4 S·m −1 ) and if the composite was made 100 µm thick. Neither of these parameters are realistic for this specific study as we focus on iron (a metal) and because 100 µm corresponds to over 10,000 repeats of the ultrathin iron layers.…”
Section: Resultsmentioning
confidence: 67%
“…[18,55] A related phenomenon that is often seen in magnetic insulators in this frequency range is the existence of surface waves. [56][57][58] Although this nonreciprocity on reflection is related to surface effects, we found that true surface waves only appear in this composite material if the conductivity was made smaller (σ < 10 4 S·m −1 ) and if the composite was made 100 µm thick. Neither of these parameters are realistic for this specific study as we focus on iron (a metal) and because 100 µm corresponds to over 10,000 repeats of the ultrathin iron layers.…”
Section: Resultsmentioning
confidence: 67%
“…By doing so, it is possible to open up gaps of non-propagating regions where surface polaritons can appear as shown in Fig. 15(f) [46]. As demonstrated recently, this rotation allows for the existence of surface waves even at zero external field which could be used as a way to enhance Goos-Hänchen shifts.…”
Section: Discussionmentioning
confidence: 77%
“…In magnets, however, the nature of the off-diagonal components is distinctively different, in which case additional nonreciprocal effects, associated with the particular form of the permeability tensor, may further modify the behavior. [33][34][35] We believe that our findings on the oriented asymmetric transmission can also be used as a potential avenue for applications on optical devices such as direction dependent electromagnetic filters.…”
Section: Final Remarksmentioning
confidence: 70%